Effectiveness of Combination of Chitosan Gel and Hydroxyapatite from Crabs Shells (Portunus pelagicus) Waste as Bonegraft on Periodontal Network Regeneration through IL-1 and BMP-2 Analysis - Asdar Gani; Risfah Yulianty; Supiaty Supiaty; Machirah Rusdy; Gustivanny Dwipa Asri; Dian Eka Satya; Ayu Rahayu Feblina; Harun Achmad (International Journal of Biomaterials)
Background. Periodontitis can be treated by regenerating periodontal tissue using a bone graft. Several natural materials such as chitosan and minerals such as hydroxyapatite can be developed to increase periodontal tissue regeneration. Chitosan has a high potential in healing wounds. Hydroxyapatite has excellent properties such as biocompatibility, osteoconductive, osteoinductive, and osteogenesis, making it an ideal material for soft and hard tissue regeneration. Chitosan and hydroxyapatite can be obtained from the shells of crustaceans, such as crabs shells (Portunus pelagicus). Objective. To assess the effectiveness of the combination of chitosan gel and hydroxyapatite powder as a bone graft on periodontal tissue regeneration in experimental animals. Periodontal tissue regeneration was assessed by expressing inflammatory cytokine gene indicators IL-1 and BMP-2. Methods. Experimental laboratory research and clinical trials with posttest only control group design. Twenty-seven Wistar rats were divided into three groups. Then the femoral bone defect was made, the positive control group was given placebo gel, the positive control group was given BATAN hydroxyapatite, and the test group was given a combination of chitosan gel and hydroxyapatite crab shells. Wistar rats were sacrificed on days 7, 14, and 21, and the femur bone was then taken for immunohistochemical analysis to determine the levels of IL-1 and BMP-2. The Kolmogorov–Smirnov test, Levene test, and one-way ANOVA analyzed the data. Results. On days 7, 14, and 21, the expression levels of IL-1 and BMP2 were significantly different between the three groups. The group added with chitosan gel and crab shell HA showed a faster decrease in IL-1 expression than the control group. BMP-2 expression increased in the test group compared to the control group. Conclusion. The combination of chitosan gel and hydroxyapatite inhibited the production of proinflammatory cytokines and increased the production of BMP-2.